2009
DOI: 10.4141/cjss08049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased residue biomass under elevated CO2 on carbon and nitrogen in soil aggregate size classes (rice-wheat rotation system, China)

Abstract: Q. 2009. Effects of increased residue biomass under elevated CO 2 on carbon and nitrogen in soil aggregate size classes (rice-wheat rotation system, China). Can. J. Soil Sci. 89: 567Á577. In order to study how soil carbon and nitrogen contents of different aggregate size fractions are affected by an increase in crop biomass and additional carbon inputs to soil due to elevated [CO 2 ], a field experiment under a free-air CO 2 enrichment (FACE) system was conducted. The experiment was set up with two CO 2 level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Our results are in agreement with the findings of Ma et al. (2009) and Wu et al. (2018), where elevated CO 2 considerably increased the macroaggregate associated carbon.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results are in agreement with the findings of Ma et al. (2009) and Wu et al. (2018), where elevated CO 2 considerably increased the macroaggregate associated carbon.…”
Section: Discussionsupporting
confidence: 94%
“…Comparatively, among the aggregate fractions, a significantly higher amount of carbon is associated with macroaggregates and surface soil than subsurface soil. Our results are in agreement with the findings of Ma et al (2009) and Wu et al (2018),…”
Section: Soil Aggregate Characteristicssupporting
confidence: 93%
See 1 more Smart Citation
“…It is predicted to continuously increase in the coming decades (Nowak et al, 2004). Elevated CO 2 (eCO 2 ) may affect plant biomass production (Ainsworth and Long, 2005; Ma et al, 2009), and residue chemical quality (Gifford et al, 2000). A number of studies reported that eCO 2 increased lignin concentration and the carbon (C)-to-nitrogen (N) ratio (C/N ratio) in plants (Torbert et al, 2000; Norby et al, 2001; Sayer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al (2000) found that the eCO 2 increased C accumulation in the physically protected SOC in a native prairie in Kansas. Moreover, Ma et al (2009) reported inputs of wheat straw grown under eCO 2 increased the SOC in a fluvo-aquic soil. However, understanding the contribution of eCO 2 -derived residue to SOC needs to reveal the microbial community structure and function that control both the SOC decomposition and stability (Sulman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%